Monitoramento contínuo de distorções utilizando sensores a lasers durante o processo de soldagem GMAW robotizdo de modelos reduzidos em escala de anéis segmentados - Jonathas Henrique Pereira (2015)
Distortions in welded components are permanent shape and dimensions changes resulting from plastic deformation that occur due to thermal stresses developed during welding process. To meet the dimensional and geometrical tolerances of project specifications is necessary to use adequate welding sequences, locking devices, and be prepared to use hot straightening operations and other manufacturing processes such as machining, that greatly increase the cost of the manufacturing process. Because of these high costs with labor and raw material to fix the welding distortion, there is great interest of the industries in better predict and control of welding distortion. Based on these premises, this work proposed a methodology for a continuous dimensional monitoring of distortions occurred during GMAW procedure of three small-scale segmented rings models. For the geometry dimensional control and flatness the three-dimensional cartesian coordinate robot system, a dial and a digital inclinometer, beforeand after the welding process were used. For continuous monitoring of distortion, laser sensors, mounted on brackets supported on the work-piece surface and a translucent screen, where the laser spots were projected, were used. With the distortion progression during welding the laser spots move around the screen in proportion to deformation occurred in the work-piece. The lasers spot movements were then recorded and the discretization of the move allowed to developgraphics that represent the work-piece behavior during the welding. With these results it was possible to know the angular distortion values during different moments of the welding procedure. Statistical calculations confirm that the final value of angular distortion measured by the monitoring system using laser sensors is equal to the average value of angular distortion checked with measuring instruments. This was an excellent result in favor of welding distortion control. This information may be used, for example, to feed back the robot trajectory so that it makes corrections during welding, thus minimizing the distortion. It also can help the welding simulation software in the numerical-experimental calibration of computational models